THE RELATIONSHIP BETWEEN FEEDING PATTERNS AND THE INCIDENCE OF STUNTING IN CHILDREN AGED 12-59 MONTHS AT THE CIUYAH VILLAGE POSYANDU, SAJIRA DISTRICT, LEBAK REGENCY IN 2023 - Mulyadi, Dede; Barkah, Asep (HEARTY, 2025)
Stunting in children is the result of failure to thrive at the age of toddlers. Malnutrition experienced in the First 1000 Days of Life (HPK) makes children more at risk for obstacles to physical growth and vulnerability of children to disease. The prevalence in Indonesia in the last 10 years shows that stunting is one of the biggest nutritional problems in toddlers. The purpose of the study was to determine the relationship between feeding patterns and the incidence of stunting in children aged 12-59 months at the Ciuyah Village Posyandu, Sajira District, Lebak Regency. This study used observational analytical research with a case control design approach. The population in this study was mothers who had children aged 12-59 months at the Ciuyah Village Posyandu, Sajira District. The respondents in this study were 82 respondents, consisting of 41 case samples (total sampling) and 41 control samples (simple random sampling). The independent variable in this study was feeding patterns. The dependent variable in this study is the incidence of stunting. Data were collected using questionnaires and children were measured in height using a stadiometer and converted into a standardized score (z-score). Data were analyzed using Chi-Square test with significance α=0.05. The results showed a significant relationship between feeding patterns and the incidence of stunting in children aged 12-59 months with a p-value of 0.012 (p = 0.012). There needs to be an improvement in feeding patterns and promotion from nurses and health workers to provide good food for children.